Aonla (Emblica officinalis) in India: A review of its improvement, production and diversified uses - A K SINGH; SANJAY SINGH; P L SAROJ; D S MISHRA; P P SINGH; R K SINGH (The Indian Journal of Agricultural Sciences, 2019)
Aonla (Emblica officinalis Gaertn), commonly called Indian gooseberry, belonging to family Euphorbiaceae, is one of the oldest known indigenous fruit tree species with wide distribution, reflecting its adaptation to wide range of edaphoclimatic conditions. It is an important fruit owing to its nutritional, therapeutical, and postharvest and industrial value. Various pharmaceutical attributes of aonla have been described in ancient treatise either in combined formulation or alone. In a bid to better utilize and improve the present genetic resource, there is a need to apprehend and appreciate the studies related to use, centre of origin and diversity, as well as the characterization, evaluation and conservation, taxonomy and systematics, phenology, floral biology and pollination. In addition to basic biology of plant, agro-techniques, propagation, canopy architecture, physiological disorders, insect-pests and diseases and their management practices, etc. have been used to conserve aonla germplasm as well as improve its production. An attempt has been made to cover aforementioned aspects with respect to aonla in this review article.